Thermodynamic investigation of asynchronous inverse air cycle integrated with compressed-air energy storage. (January 2022) - Giannetti, Niccolò; Milazzo, Adriano; Saito, Kiyoshi
Highlights: Thermodynamic analysis of a novel asynchronous inverse air cycle integrated with CAES. The system benefits of daily variations in ambient temperature and electricity price. The storage vessel is used as a heat exchanger between compressed air and environment. Dehumidification, high-temperature heating, and low-temperature cooling are performed. Abstract: A novel integrated system for heating, cooling, and compressed-air energy storage (CAES) is analysed from a thermodynamic perspective. The system is based on asynchronous air compression and expansion to take advantage of daily ambient temperature oscillations, electricity pricing variations, and the discontinuous availability of renewable sources. Furthermore, the integration of CAES with an open inverse air cycle eliminates grid and generator losses incurred in the supply of thermal energy for end-use heating and cooling applications. The novelty is represented by using the storage vessel as a heat exchanger interfaced with the external environment, which acts as a heat source or sink in relation to the ambient conditions and phase of operation. To ensure wide applicability, the analysis is kept on a fundamental level, without explicit reference to specific technical details of the components. The sole technical premise is represented by a commercially available vessel for air storage featuring a volume of 10 m 3 and a maximum operating pressure of 12 bar. This choice may be interpreted as a constituent unit for a modular system that can be easily scaled-up to the required capacity. Two configurations are proposed: one for air conditioning and sanitary water production, and the other for refrigeration. The first configuration yields a global COP of 1.49 and a second law efficiency of 0.149. The second one may produce heating at temperatures as high as 400 °C and refrigeration at -90 °C with a global COP of 1.30 and a second law efficiency of 0.192. The effects of losses in the compressor, expander, and heat exchangers, as well as heat transfer in storage vessel, are discussed, accounting also for condensation/evaporation due to the air humidity.